Minimal residual disease as biomarker for optimal biologic dosing of ARA‐C in patients with acute myeloid leukemia. Issue 2 (24th November 2014) - Maurillo, Luca; Buccisano, Francesco; Piciocchi, Alfonso; Del Principe, Maria Ilaria; Sarlo, Chiara; Di Veroli, Ambra; Panetta, Paola; Irno‐Consalvo, Maria; Nasso, Daniela; Ditto, Concetta; Refrigeri, Marco; De Angelis, Gottardo; et al.
<x xml:space="preserve">Abstract</x> We assessed by flow cytometry minimal residual disease (MRD) in patients with acute myeloid leukemia (AML) given standard‐dose (SDAC) and high‐dose ARA‐C (HDAC) regimens. Of 163 patients enrolled, 130 (median age, 45 years; range, 18–59 years) qualified for analysis, all achieving complete remission after treatment with SDAC (n = 78) or HDAC (n = 52) plus etoposide and daunorubicin. Consolidation consisted of intermediate‐dose ARA‐C and daunorubicin. MRD negativity was significantly more frequent in the SDAC vs. HDAC arm after both induction (37% vs. 15%, P = 0.007) and consolidation (44% vs. 18%, P = 0.002). Respective median residual leukemic cell counts with SDAC and HDAC use were 1.5 × 10−3 and 4 × 10−3 (P = 0.033) after induction and 5.7 × 10−4 and 2.9 × 10−3 (P = 0.008) after consolidation. Based on ARA‐C schedule and post‐consolidation MRD status, the four patient groups (SDAC‐MRD−, HDAC‐MRD−, SDAC‐MRD+, and HDAC‐MRD+) displayed 5‐year overall survival rates of 60%, 33%, 24%, and 42% (P = 0.007), respectively, with 24%, 35%, 74%, and 48% (P < 0.0001) respective cumulative incidence of relapse estimates. MRD may serve as a biomarker for optimal biologic dosing of ARA‐C, and SDAC regimen appears to yield more frequent MRD negativity. Am. J. Hematol. 90:125–131, 2015. © 2014 Wiley Periodicals, Inc.